Novel long-acting antagonists of muscarinic ACh receptors - Randáková, Alena; Rudajev, Vladimír; Doležal, Vladimír; Boulos, John; Jakubík, Jan (British journal of pharmacology, 2018)
BACKGROUND AND PURPOSE: The aim of this study was to develop potent and long-acting antagonists of muscarinic ACh receptors. The 4-hexyloxy and 4-butyloxy derivatives of 1-[2-(4-oxidobenzoyloxy)ethyl]-1,2,3,6-tetrahydropyridin-1-ium were synthesized and tested for biological activity. Antagonists with long-residence time at receptors are therapeutic targets for the treatment of several neurological and psychiatric human diseases. Their long-acting effects allow for reduced daily doses and adverse effects. EXPERIMENTAL APPROACH: The binding and antagonism of functional responses to the agonist carbachol mediated by 4-hexyloxy compounds were investigated in CHO cells expressing individual subtypes of muscarinic receptors and compared with 4-butyloxy analogues. KEY RESULTS: The 4-hexyloxy derivatives were found to bind muscarinic receptors with micromolar affinity and antagonized the functional response to carbachol with a potency ranging from 30 nM at M1 to 4 μM at M3 receptors. Under washing conditions to reverse antagonism, the half-life of their antagonistic action ranged from 1.7 h at M2 to 5 h at M5 receptors. CONCLUSIONS AND IMPLICATIONS: The 4-hexyloxy derivatives were found to be potent long-acting M1 -preferring antagonists. In view of current literature, M1 -selective antagonists may have therapeutic potential for striatal cholinergic dystonia, delaying epileptic seizure after organophosphate intoxication or relieving depression. These compounds may also serve as a tool for research into cognitive deficits.
Keywords: receptory muskarinové; Structure-Activity Relationship; molekulární struktura; CHO Cells; antagonisté muskarinových receptorů; Molecular Structure; vztah mezi dávkou a účinkem léčiva; vztahy mezi strukturou a aktivitou; Cricetulus; kultivované buňky; Animals; CHO buňky; zvířata; pyridiny; Pyridines; karbachol; Cells, Cultured; Carbachol; Receptors, Muscarinic; Dose-Response Relationship, Drug; Muscarinic Antagonists